INNOVATIVE DIAGNOSTIC TECHNOLOGIES AND TARGETED THERAPEUTICS IN HYPERTROPHIC CARDIOMYOPATHY: IMPLICATIONS FOR PERSONALIZED PATIENT CARE - Anna Woźniak; Aleksandra Grygorowicz; Klaudia Baran; Michał Ględa; Michał Szyszka; Weronika Radecka; Weronika Kozak; Agnieszka Szreiber; Karol Grela; Karolina Nowacka; Kamil Jabłoński (International Journal of Innovative Technologies in Social Science, 2025)
Background: Hypertrophic cardiomyopathy (HCM) is a genetic myocardial disease characterized by unexplained left ventricular hypertrophy, cardiomyocyte disarray, and fibrosis. It presents a broad spectrum of symptoms, from asymptomatic cases to heart failure, arrhythmias, and sudden death. Advances in diagnostics and treatment have significantly improved clinical management. Methods: This review examines hypertrophic cardiomyopathy, focusing on its pathophysiology, genetics, clinical features, and recent advances in diagnosis and treatment. It highlights new imaging and genetic testing methods, risk assessment strategies, emerging myosin inhibitors, and prospects for gene therapy, including current trial data and associated challenges. Results: Echocardiography and cardiac MRI are essential for assessing left ventricular hypertrophy and fibrosis. Genetic analysis identifies sarcomere gene mutations. Cardiac myosin inhibitors, combined with conventional therapy and septal reduction, reduce outflow tract gradients, alleviate symptoms, and improve quality of life. Surgical myectomy, alcohol septal ablation, and ICDs relieve symptoms and lower sudden death risk in high-risk patients. Digital tools enable individualized treatment monitoring. Conclusion: Advances in genetics, imaging, and targeted therapies have improved HCM management, enabling personalized treatment and reducing the risk of sudden death. Future studies should evaluate long-term efficacy and integration with genetic testing and telemedicine.